Change in the coding of interaural time difference along the tonotopic axis of the chicken nucleus laminaris - Palanca-Castan, Nicolas; Köppl, Christine (Frontiers in Neural Circuits, 2015)
Interaural time differences (ITDs) are an important cue for the localization of sounds in azimuthal space. Both birds and mammals have specialized, tonotopically organized nuclei in the brain stem for the processing of ITD: medial superior olive in mammals and nucleus laminaris (NL) in birds. The specific way in which ITDs are derived was long assumed to conform to a delay-line model in which arrays of systematically arranged cells create a representation of auditory space with different cells responding maximally to specific ITDs. This model was supported by data from barn owl NL taken from regions above 3 kHz and from chicken above 1 kHz. However, data from mammals often do not show defining features of the Jeffress model such as a systematic topographic representation of best ITDs or the presence of axonal delay lines, and an alternative has been proposed in which neurons are not topographically arranged with respect to ITD and coding occurs through the assessment of the overall response of two large neuron populations, one in each hemisphere. Modeling studies have suggested that the presence of different coding systems could be related to the animal’s head size and frequency range rather than their phylogenetic group. Testing this hypothesis requires data from across the tonotopic range of both birds and mammals. The aim of this study was to obtain in vivo recordings from neurons in the low-frequency range (<1000 Hz) of chicken NL. Our data argues for the presence of a modified Jeffress system that uses the slopes of ITD-selective response functions instead of their peaks to topographically represent ITD at mid- to high frequencies. At low frequencies, below several 100 Hz, the data did not support any current model of ITD coding. This is different to what was previously shown in the barn owl and suggests that constraints in optimal ITD processing may be associated with the particular demands on sound localization determined by the animal’s ecological niche in the same way as other perceptual systems such as field of best vision.